Economic Ordering Policy for VAR Deterioration Model with Non-stationary Two-warehouse Inventory and Demand - Abdullah Mohammed Alshami; Aniket Muley (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2020)
AbstractThis paper adopts the two-warehouse inventory, determination on the first run-time and VAR (Vector Auto Regression) deterioration model. The optimal EOQ in the interval of the finite horizon is determined under critical considerations. The non-stationary two-warehouse inventory, i.e. the inventory and initial inventory are non-stationary at level, but stationary after lag difference similar to demand (demand and initial demand). The output of the proposed model represented the optimal order quantity and optimal first run-time, the optimal total cost as integration of first order with the significant trend and intercept. The optimal demand is decreased during more risk as a deterioration variable to reduce the quantity in the stock. The initial demand is stationary after a first lag and the demand is stationary.Keywords: initial inventory; optimal of first run-time; EOQ (Economic Ordering Quantity); total cost function (TC). AbstrakPenelitian ini mengadopsi inventori dengan dua gudang penyimpanan, penentuan pada waktu run (run-time) awal, dan model deteriorating VAR (Vector Auto Regression). Nilai optimal EOQ dalam interval horizon berhingga ditentukan dengan pertimbangan kritis. Inventori dengan dua gedung yang tidak stasioner, yaitu inventori dan inventori awal tidak stasioner pada level, tetapi stasioner setelah perbedaan lag seperti halnya pada permintaan (permintaan dan permintaan awal). Hasil dari model yang diajukan menunjukkan nilai orde yang optimal dan waktu run awal yang optimal, total biaya optimal sebagai integrasi dari orde pertama dengan tren dan intercept yang signifikan. Permintaan optimal mengalami penurunan ketika lebih banyak risiko sebagai variabel deteroriating untuk mengurangi jumlah dalam stok. Permintaan awal menunjukkan stasioner setelah perbedaan lag pertama dan permintaan juga stasioner.Kata kunci: inventori awal; optimal run-time awal; EOQ (Economic Ordering Quantity); fungsi biaya total.